1994
DOI: 10.1007/bf01401451
|View full text |Cite
|
Sign up to set email alerts
|

Management of dissecting aneurysms of the posterior circulation

Abstract: We analysed the clinical presentation, treatment and outcome of our own 36 cases of posterior circulation dissecting aneurysms (DA) and discussed the surgical indications and procedures regarding posterior fossa DA. Twenty one cases were male, 15 cases were female. Their mean age was 54 +/- 14 years. Clinical manifestations were subarachnoid haemorrhage (SAH) in 14 cases (39%) and ischaemic attacks in 22 cases (61%). Three of 14 SAH cases had rebleeding in the acute stage. Angiographic findings were aneurysmal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Thirty patients were admitted with SAH, 24 were admitted with brain stem ischemia, eight were asymptomatic, and two had an unknown diagnosis. Most of intracranial dissections result in ischemia as the cause of death, 6) but we found that SAH slightly outnumbered ischemia as the main cause of death. 4,17) Recurrence of bleeding in the acute stage accounted for eight cases (26.1%), which is similar to that reported for dissecting vertebral artery aneurysms (28%).…”
Section: Discussionmentioning
confidence: 51%
“…Thirty patients were admitted with SAH, 24 were admitted with brain stem ischemia, eight were asymptomatic, and two had an unknown diagnosis. Most of intracranial dissections result in ischemia as the cause of death, 6) but we found that SAH slightly outnumbered ischemia as the main cause of death. 4,17) Recurrence of bleeding in the acute stage accounted for eight cases (26.1%), which is similar to that reported for dissecting vertebral artery aneurysms (28%).…”
Section: Discussionmentioning
confidence: 51%
“…However, details of the background and the optimal management for cerebral artery dissection are still unknown (10).…”
Section: Discussionmentioning
confidence: 99%
“…Probability of rebleeding and morbidity/ mortality rates of IDAs of the VB circulation were reported as high as 71 and 50 %, respectively [4,17,18,73,94,97,145,160]. Kawaguchi and associates [62] reported in their series of VA dissecting aneurysms 21 % rebleeding rate during the first 72 h with 100 % mortality. Yamaura et al [171] reported 24 % of rebleeding in time period from third to 17th postictus day with 80 % mortality rate.…”
Section: Prognosismentioning
confidence: 95%